2002
DOI: 10.1016/s0925-4439(02)00141-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo treatment with stobadine prevents lipid peroxidation, protein glycation and calcium overload but does not ameliorate Ca2+-ATPase activity in heart and liver of streptozotocin-diabetic rats: comparison with vitamin E

Abstract: Hyperglycemia leads to excess production of reactive oxygen species (ROS), lipid peroxidation and protein glycation that may impair cellular calcium homeostasis and results in calcium sequestration and dysfunction in diabetic tissues. Stobadine (ST) is a pyridoindole antioxidant has been postulated as a new cardio- and neuroprotectant. This study was undertaken to test the hypothesis that the treatment with ST inhibits calcium accumulation, reduces lipid peroxidation and protein glycation and can change Ca2+,M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 42 publications
6
57
0
Order By: Relevance
“…The albumin level may decrease in rats as a disorder of the liver function after furan exposure; there are studies confirming that chemicals cause a reduction of albumin and total protein levels (22). In previous studies, researchers observed that diabetes caused an increase in the serum levels of total cholesterol and triglyceride (23). Thus, increased parameters can be due to the effects of diabetes on the permeability of membranes of hepatic cells (24).…”
Section: Discussionmentioning
confidence: 98%
“…The albumin level may decrease in rats as a disorder of the liver function after furan exposure; there are studies confirming that chemicals cause a reduction of albumin and total protein levels (22). In previous studies, researchers observed that diabetes caused an increase in the serum levels of total cholesterol and triglyceride (23). Thus, increased parameters can be due to the effects of diabetes on the permeability of membranes of hepatic cells (24).…”
Section: Discussionmentioning
confidence: 98%
“…Although it has been reported that stobadine has free radical scavenging properties both in vivo and in vitro [4] and that it inhibits STZ-induced lipid peroxidation [7], the mechanism of inhibition of the effects of diabetes on leukocyte free radical release is not known from the present study. We have shown that stobadine reduced hyperglycemia which may involve the restoration of the leukocyte CL response in our study.…”
Section: Discussionmentioning
confidence: 69%
“…We have shown that stobadine reduced hyperglycemia which may involve the restoration of the leukocyte CL response in our study. Stobadine has been shown to suppress the STZ-induced elevation of the blood glucose levels in rats [7] and the alloxan-induced hyperglycemia in mice in a dose-and time-dependent manner [13]. It has been demonstrated in a recent study [14] that stobadine was able to restore the enzymatic activities related to pentose phosphate pathway and glutathionedependent metabolism in brain and peripheral organs of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact mechanism(s) of the effects of the both antioxidants on abnormal intracellular calcium regulation of diabetic heart and liver are not fully known. It was also observed that by the using both antioxidants together, hyperglycemia-induced oxidative stress can be controlled effectively (Pekiner et al, 2002).…”
Section: In Vivo Inhibition Of Protein Glycationmentioning
confidence: 99%